Project, program and portfolio management as modes of organizing: Theorising at the intersection between mergers and acquisitions and project studies - Geraldi Joana; Teerikangas Satu; Birollo Gustavo (Elsevier Ltd, 2022)
Although the management of mergers and acquisitions (M&As) and of projects are connected in practice, they remain disjoined in academia. In this paper, we conceptually bridge the literature on projects and M&As to discuss the transitory nature of organisations by mobilising the concepts of project, programme, and portfolio as alternative modes of organising M&As. As a project, the managerial effort in M&A focuses on completion on time and budget. As a programme, M&As are managed as complex processes of convergence between organisations. As a portfolio, M&A management is part of the ongoing integration efforts within organisations that have grown via M&As. Our contribution to project studies is to position projects, programmes, and portfolios as modes of organising, hence, not as phenomena but as managerial choices used to shape strategic change initiatives, such as M&As. We conclude with implications beyond project studies, thereby drafting a project-based theory of the firm.